Intensity modulation function and beam orientation optimization in conformal radiotherapy treatment planning - Lim, Chong Jen. (2008)
In applying Genetic Algorithm to CRTP, we developed a specific Radiotherapy Genetic Algorithm (R-GA) for the purpose of inverse planning, which essentially means computing an optimum set of beam parameters that will produce a dose distribution conformal to that of the prescribed one.